(untitled) (Delta Medical College Journal, 2016)
Background: In patients with acute coronary syndrome (ACS), Cardiac Troponin I (cTnI) elevation is indicative of myocardial damage. After acute myocardial infarction (AMI), level of Pro-BNP rises rapidly during the first 24 hours and tends to stabilize thereafter. Objective: The present study tried to explore the pattern of multiple cardiac biomarkers (cTnI, CK-MB, Pro-BNP, SGOT and LDH) in newly diagnosed acute ST-elevation myocardial infarction (STEMI) patients without clinical symptoms of heart failure. Materials and method: This was a prospective study. Total 82 acute STEMI patients were recruited purposively from National Institute of Cardiovascular Disease (NICVD), Dhaka, Bangladesh, within 24 hours of symptoms having normal serum creatinine level. cTnI and pro-BNP elevation were defined >1mg/mL and >125 pg/mL respectively. The study population was sub grouped according to age: group A (<40 years), group B (40-50 years), group C (>51-60 years) and group D (>60 years). Results: The mean±SD age of patients was 53.3±11.6 years and 42.70% population belonged to relatively younger age group (group B). Smoking was found on the top of the list (73.20%) as a risk factor. There was no difference among the groups regarding atherosclerotic marker and no other cardiac markers except pro-BNP. Only Pro-BNP (pg/mL) showed gradual and progressive increment with increasing age. No significant difference was observed between CRP positive and negative groups in different age groups (cut off value <6mg/dL). Group B (40-50 years) seems to be the most vulnerable as the anterior and the extensive anterior myocardial infarctions (worst prognosis) were highest in this group. Conclusion: Worst prognosis is associated with increased age and raised pro-BNP level. Delta Med Col J. Jul 2016 4(2): 55-60